Eco-anxiety, knowledge and action in primary school-aged children in East London - Dennis Ougrin; Francois van Loggerenberg; Imogen I. Hensler; Khushi Patel; Julia Michalek; Callum Ritchie; Jennifer Y.F. Lau (BMJ Paediatrics Open)
Eco-anxiety refers to negative feelings around climate change, associated with distress and concern about the future. As there are minimal data on eco-anxiety in pre-adolescent children, here, we measured worries, knowledge and commitment to action in primary school-aged children in East London, an area characterised by high child poverty levels and ethnic diversity. Approximately half of the children worry about and are aware of global warming. We also found a correlation between worries and knowledge, and between worries and taking action. While these data are limited by a cross-sectional design and by the use of single-item self-reports of these constructs, nonetheless, greater engagement of pre-adolescent children in discussions around climate change is called for.